2020
DOI: 10.1016/j.surg.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The Cushing reflex and the vasopressin-mediated hemodynamic response to increased intracranial pressure during acute elevations in intraabdominal pressure

Abstract: Background: Abdominal compartment syndrome has been linked to detrimental hemodynamic side effects that include increased intracranial pressure and diminished renal function, but the mechanisms behind this continue to be elucidated. In this study, we sought to investigate any direct association between acute elevations in intra-abdominal pressure and intracranial hypertension during experimentally induced abdominal compartment syndrome and between acutely elevated intracranial pressure and the hemodynamic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Literature review did not yield any studies that were pertinent to postoperative effects of urinary catheter placement following ESBS. Previous studies have found that increased intra‐abdominal pressure, which can be directly affected by bladder volume, can result in increased ICP and vasopressin release via the Cushing reflex 60–62 . This reasoning can be used to postulate that urinary catheters may be used during the postoperative period to prevent ICP shifts by preventing urinary retention.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Literature review did not yield any studies that were pertinent to postoperative effects of urinary catheter placement following ESBS. Previous studies have found that increased intra‐abdominal pressure, which can be directly affected by bladder volume, can result in increased ICP and vasopressin release via the Cushing reflex 60–62 . This reasoning can be used to postulate that urinary catheters may be used during the postoperative period to prevent ICP shifts by preventing urinary retention.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have found that increased intra-abdominal pressure, which can be directly affected by bladder volume, can result in increased ICP and vasopressin release via the Cushing reflex. [60][61][62] This reasoning can be used to postulate that urinary catheters may be used during the postoperative period to prevent ICP shifts by preventing urinary retention. Aggregate grade of evidence: D (no dedicated studies)…”
Section: Urinary Catheter Usementioning
confidence: 99%
“…We additionally found that patients with gastrointestinal diseases were more likely to require a neurosurgical procedure. Gastrointestinal processes that increase intraabdominal pressure have long been associated with increased intracranial pressure, especially as noted in severe disease processes such as abdominal compartment syndrome [ 13 ]. Although gastrointestinal processes were not stratified by specific disease in our cohort, the underlying principle of increased intra-abdominal pressure, either due to pain from the underlying disease or the disease itself, may biologically be related to increased intracranial pressure leading to additional neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intrathoracic pressure elevates the central venous pressure, leading to diminished venous circulation through the jugular vein. This increases intracranial pressure [ 46 , 47 ].…”
Section: Impact On Intracranial Pressurementioning
confidence: 99%